A Radical-Free Approach to Teeth Whitening - Mauro Pascolutti; Dileusa de Oliveira (MDPI AG, 2021)
Background: Traditional bleaching agents based on hydrogen peroxide (HP) or carbamide peroxide (CP) have adverse soft and hard tissue effects. Objectives: This study tested a novel formulation of phthalimidoperoxycaproic acid (PAP) with additives to optimise its safety and effectiveness. Methods: A novel gel (PAP+) was formulated. Laboratory studies assessed effects of six 10-minute exposures to PAP+ vs. commercial CP and HP gels, using surface profilometry and microhardness. The effectiveness of PAP+ in vitro against complex polyphenol stains on enamel was compared to 6% HP. Results: Unlike HP gels, PAP+ gel did not erode enamel. Unlike both CP and HP gels, PAP+ gel did not reduce the surface microhardness of enamel. PAP+ gel on used on polyphenol stains was superior to 6% HP. In this model, six repeated 10-minute treatments with PAP+ gel could improve the shade by approximately eight VITA® Bleachedguide shades. Conclusions: These laboratory results support the safety and effectiveness of this new PAP formula and its use as an alternative to CP and HP with superior safety and effectiveness.